Does Fair Value Accounting Exacerbate the Procyclicality of Bank Lending? - XIE, BIQIN (Journal of Accounting Research, 2016)
ABSTRACT This study investigates whether fair value accounting contributes to the procyclicality of bank lending. Using banks’ approval/denial decisions on residential mortgage applications to capture banks’ supply of credit, I find no evidence that fair value accounting has procyclical effects on bank lending over the past two business cycles. I further identify two reasons for this result. First, the main accounting item distinguishing fair value accounting from historical cost accounting—unrealized gains and losses on available‐for‐sale securities—does not affect lending decisions. Second, unrealized gains and losses on available‐for‐sale securities are not procyclical, as the risk‐free interest rate rises during some expansionary periods, resulting in unrealized losses, while the risk‐free interest rate (and sometimes the default spread) falls during some recessionary periods, resulting in unrealized gains.